Knowledge & Attitude regarding Stem Cells research and its applications among Residents of a Tertiary Care Hospital in Karachi, Pakistan - Ambreen Unar; Syed Akbar Abbas; Abdul Basit Shah Vardag; Soubia Akhtar; Ozair Awan; Ainulakbar Mughal (Journal of the Pakistan Medical Association, 2023)
Objective: The importance and potential of the use of stem cells as therapeutic tools is enormous and therefore, health professionals should be expected to have thorough knowledge and a positive attitude towards their utilization in medical practice. Hence this study was carried out to report and assess the knowledge and attitude regarding stem cell in our region. Methodology: The study was conducted amongst the residents employed at the Aga Khan University hospital, Karachi Pakistan from September-October 2022 with a sample size of 57. Results: Amongst our survey participants, 33 (54.2%) responded with a score of 48 and above (i.e., 60% or above); 25 (40.9%) of the study participants scored between 50-60% only 3 (4.9%) had a score 40-50% Conclusion: Our survey shows a reasonable level of knowledge of the generic principles and implications Stem cell therapy amongst the residents Keywords: Stem cell, Head and Neck, Risk, Cell, Tissue, Therapy